2012
DOI: 10.1111/iji.12006
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of filaggrin null mutations in Croatia and their relation with allergic diseases

Abstract: Filaggrin gene (FLG) null mutations are considered associated with atopic dermatitis. This study was conducted to determine the prevalence of FLG null mutations R501X, 2282del4, R2447X and S3247X in the Croatian population and their role in the occurrence of allergic diseases including atopic dermatitis, allergic rhinitis, asthma and allergic contact dermatitis (ACD). Study enrolled 440 freshmen with defined allergic diseases by means of both present symptoms in International Study of Asthma and Allergies in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
5
16
1
Order By: Relevance
“…It can be speculated that population-specific individual risk factors may contribute to this difference. Notably, the prevalence of filaggrin null mutations, which constitute a recognized susceptibility factor for the development of irritant contact dermatitis (3), differs significantly between populations, with a marked decrease from northern to southern Europe (28)(29)(30)(31)(32). The low prevalence of filaggrin null mutations found in Croatia (28) may render our cohort of apprentices less prone to irritant skin changes, and it would be worth testing this hypothesis in further epidemiological studies.…”
Section: Discussionmentioning
confidence: 97%
“…It can be speculated that population-specific individual risk factors may contribute to this difference. Notably, the prevalence of filaggrin null mutations, which constitute a recognized susceptibility factor for the development of irritant contact dermatitis (3), differs significantly between populations, with a marked decrease from northern to southern Europe (28)(29)(30)(31)(32). The low prevalence of filaggrin null mutations found in Croatia (28) may render our cohort of apprentices less prone to irritant skin changes, and it would be worth testing this hypothesis in further epidemiological studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, our previous study revealed a low frequency of common FLG null mutations in the Croatian population, suggesting that these mutations do not have a significant impact on the development and course of skin diseases, including ACD, in the Croatian and other populations with low penetrations of FLG mutations [38]. The data indicate a decreasing north-south gradient of R501X and 2282del4 FLG mutation frequencies in Europe with a lower penetration of FLG mutations in the Italian and Croatian population when compared to Ireland, the UK and Germany [38,39,40]. The results of the present study are in line with these suggestions.…”
Section: Discussionmentioning
confidence: 99%
“…The number of responders was 440, and for the purpose of this study 437 participants from whom buccal swabs were collected [55] were recontacted by phone in 2014 and asked to accept via mail a consent form for this study, i.e. consent for the analysis of additional cytokine polymorphisms from their buccal swabs.…”
Section: Methodsmentioning
confidence: 99%